Efektivitas Unsur Pembentuk Digital Video Marketing terhadap Viralitas dan Citra Destinasi Pariwisata Bali - Herry Arianto (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Digital video marketing has proven to be one of the most effective approaches, as it combines visual, narrative, and emotional elements into a single medium. This study aims to analyze the effectiveness of digital video marketing components in influencing the virality level and destination image of Bali’s tourism sector. The theoretical foundation applied in this research includes the Integrated Marketing Communication Theory and the Destination Image Theory. The research employs a qualitative descriptive approach using non-participatory observation of three Bali promotional videos published through social media accounts such as UNILAD Adventure, Bali Go Live, and Wonderful Indonesia. Data were analyzed through an interactive analysis model consisting of reduction, display, and verification stages, complemented by content analysis on video elements. The results show that all video components function effectively in enhancing audience attention and engagement, strengthening emotional resonance, and shaping Bali’s image as an exotic, spiritual, and culturally rich destination. The elements of content, cinematic technique, and traditional audio were found to have a dominant influence in generating engagement and expanding digital reach organically. This study recommends strategic collaboration between government bodies, creative industry players, and digital creators to produce consistent, authentic, and sustainable video content for Bali’s tourism promotion.